A nanopillar-structured perovskite-based efficient semitransparent solar module for power-generating window applications. Issue 3 (24th December 2019) - Kwon, Hyeok-Chan; Ma, Sunihl; Yun, Seong-Cheol; Jang, Gyumin; Yang, Hyunha; Moon, Jooho
Abstract : An efficient large-area semitransparent solar module is demonstrated using a nanopillar perovskite absorber. A 40.8 cm 2 semitransparent solar module with a PCE of 9.04%, AVT of 30.2%, and high GFF of 95.6% is obtained. Abstract : Developing large-area semitransparent solar modules is an essential step in the commercialization of semitransparent photovoltaic technologies. However, it has not yet benefited from the significant scientific advances in the field of perovskite solar cells, probably owing to the difficulties in achieving a highly uniform and large-scale semitransparent light absorber. Herein, a semitransparent solar module comprising anodized aluminum oxide (AAO) template-derived vertically aligned one-dimensional nanopillar CH3 NH3 PbI3− x Cl x perovskite is reported, which has a uniform semitransparent absorber with a large area of 40.8 cm 2 and exhibits a geometrical fill factor of 95.6%. The AAO scaffold facilitates the formation of a homogeneous perovskite morphology and allows for reduced light reflection. The uniform nanopillar-structured perovskite-based device exhibits enhanced electrical properties owing to the restricted carrier path. Our optimized nanopillar-based semitransparent solar module with nine sub-cells shows a power conversion efficiency of 9.04% and an average visible-light transmittance of 30.2%, clearly exhibiting potential for practical power-generating window applications.